Modeling the Enablers and Barriers to Effective E-learning: A TISM Approach - Panackal, Nehajoan; Rautela, Sonica; Sharma, Adya (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Abstract: The drastic change in the technological environment has transformed the entire world including the education sector which was and is largely dominated by classroom teaching. In the last decade, a new entrant in the education sector has been e-learning. The COVID-19 pandemic has forced educational institutes to look at e-learning as a path to continue the learning process. The present paper aims to propose a model highlighting the enablers that encourage the smooth and effective delivery of e-learning process and highlight the barriers that cause hurdles in the effective delivery of e-learning. The researchers have followed the Total Interpretive Structural Modelling and Fuzzy Matriced’ Impacts Croise's Multiplication Appliquée a UN Classement (MICMAC) analysis approach of extant literature review, expert opinion and multiple iterations to arrive at the proposed model. The findings of the present research study show the linkages between the identified enablers: institutional culture, institutional capability and support, flexibility in the teaching-learning process, e-readiness, motivation, knowledge management practices, and technology. Knowledge management practices that include practices of capturing knowledge and sharing knowledge have emerged as the most significant enabler of e-learning. The model on barriers to e-learning shows the relationship between lack of required skills, lack of access to technology, quality concerns, time as a barrier, learner engagement as barriers to effective e-learning. Modelling of enablers and barriers and effective e-learning is a less explored area, particularly in the Indian context with special emphasis on the pandemic. The study was carried out to address this research gap.